Expression, purification, crystallization and preliminary X-ray analysis of the human NORE1 SARAH domain - Kim, Hye Jin (International Union of Crystallography, 2012)
NORE1 is an important tumour suppressor in human cancers that interacts with the pro-apoptotic protein kinase MST1/2 through SARAH domains. The SARAH domain (residues 366–413) of human NORE1 was expressed in Escherichia coli, purified and crystallized using the hanging-drop vapour-diffusion method. The crystal diffracted to 2.7 Å resolution and belonged to space group P6(1)22, with unit-cell parameters a = b = 73.041, c = 66.092 Å, α = β = 90, γ = 120°.